1991
DOI: 10.1017/s0033291700020407
|View full text |Cite
|
Sign up to set email alerts
|

Blunting of neuroendocrine responses to infusion of L-tryptophan in women with perimenstrual mood change

Abstract: SYNOPSISThe neuroendocrine response to L-tryptophan infusion was measured at two stages of the menstrual cycle, premenstrually and postmenstrually, in 13 women with and 13 women without premenstrual depression (the MC and NMC groups respectively). Previous studies have shown that in non-depressed women, this challenge test results in an increase in circulating prolactin and growth hormone. In depressed women both responses are blunted. In this study the growth hormone and cortisol responses were smaller in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(37 citation statements)
references
References 21 publications
4
33
0
Order By: Relevance
“…All tests performed in Table 2 not a surprising find. It is consistent with the results obtained in other biological challenge studies of PMDD women (Bancroft et al 1991;Harrison et al 1989) and leads us to the state-versus-trait issue (Bancroft 1993), which needs to be addressed in future investigations. The differences in behavioral and physiological responses between placebo and CCK-4 injections in healthy volunteers are consistent with those already discussed in many studies (Bradwejn et al 1991;De Montigny 1989;Jerabek et al 1995).…”
Section: Discussionsupporting
confidence: 90%
“…All tests performed in Table 2 not a surprising find. It is consistent with the results obtained in other biological challenge studies of PMDD women (Bancroft et al 1991;Harrison et al 1989) and leads us to the state-versus-trait issue (Bancroft 1993), which needs to be addressed in future investigations. The differences in behavioral and physiological responses between placebo and CCK-4 injections in healthy volunteers are consistent with those already discussed in many studies (Bradwejn et al 1991;De Montigny 1989;Jerabek et al 1995).…”
Section: Discussionsupporting
confidence: 90%
“…First, as reviewed above, allopregnanolone negatively modulates the HPA axis in animal models, and although null findings have been reported (Su et al, 1997;Bloch et al, 2000;Lombardi et al, 2004) where diagnosis-related differences exist, they suggest blunted HPA axis function in PMDD. For example, a number of studies have reported lower circulating ACTH or cortisol concentrations in PMDD women (Rabin et al, 1990;Redei & Freeman, 1993;Girdler et al, 1998), increased ACTH response to ovine CRF (consistent with lower endogenous CRF; Rabin et al, 1990), a delayed (Steiner et al, 1999) or blunted HPA axis response to serotonergic agents (Bancroft et al, 1991;Su et al, 1997), and the absence of the normal plasma cortisol and ACTH response to exercise stress in the luteal phase that is seen in non-PMDD women (Roca et al, 2003). More compelling evidence that the greater allopregnanolone concentrations that we observed in PMDD women might negatively modulate HPA axis function in that population comes from our own results reported in Girdler et al (2001), documenting significantly lower plasma cortisol concentrations in the PMDD women than the controls (5.8±0.6 vs. 7.7±0.7 μg/dL, respectively; P<0.05).…”
Section: Hpa Axis and Gaba A Receptor Function In Pmddmentioning
confidence: 99%
“…In fact, when their 5-HT was lowered by TD during the premenstrual phase, healthy women were found to behave more aggressively in response to provocation than after a control drink [Bond et al, 2001]. Several studies have indicated a difference in the sensitivity of the 5-HT system in women with premenstrual disorders [Bancroft et al, 1991;Fitzgerald et al, 1997;Kouri and Halbreich, 1997;Menkes et al, 1994], which may make them more vulnerable to cyclical hormonal changes [Rubinow et al, 1998]. …”
Section: Introductionmentioning
confidence: 99%